An Attempt to Improve Teachers' Commitment to Carrying Out Their Duties Through Coaching Activities at SDN 007 Sialang Godang Bandar Petalangan in Pelalawan - Yayuk Indarwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines efforts to increase teachers’ commitment in carrying out their professional duties through coaching activities at SDN 007 Sialang Godang, Bandar Petalangan, Pelalawan Regency. The focus of the research is based on the identification and limitation of problems related to teachers’ commitment in performing their responsibilities. The research employed a school action research design conducted at SDN 007 Sialang Godang under the supervision of the school principal, as this approach supports the principal’s role in improving teacher commitment through coaching. The study was carried out in two cycles over approximately two months, starting in September 2022 and ending in October 2022. Based on data analysis and discussion, the results show that teachers’ commitment in carrying out their duties reached 64% in Cycle I, which was categorized as good, and increased to 84% in Cycle II, also categorized as good. These findings indicate that coaching activities were effective in increasing teachers’ commitment in carrying out their professional duties at SDN 007 Sialang Godang, Bandar Petalangan, Pelalawan Regency.